Relative/Patients’ Satisfaction of Nurses Services in Federal Neuro-Psychiatric Hospital, Calabar; Within 2022 - Umoh, Edet O.; Endra, Michael E. (British Journal of Healthcare and Medical Research, 2024)
The study was conducted to investigate relative/patients’ satisfaction to nursing services in Federal Neuro-Psychiatric Hospital, Calabar from January to December, 2022. Three (3) research questions were raised and one hypothesis was formulated to guide the study. A cross sectional research design was used to study 204 relatives who came to retrieve their recovering member home. Instrument for data collection called Relative/Patient Satisfaction of Nursing Services (RSNS) was constructed in line with research questions; it was also validated with face validation and its reliability ascertained with split-half reliability test and a reliability coefficient of 0.885 was obtained. Collected data were analyzed with descriptive statistics using frequency counts, simple percentage, mean and standard deviation, while hypothesis was tested with use of One Way Analysis of Variance (ANOVA). Obtained results were presented in charts, tables and graphs. Finding revealed that majority of the respondents waited within 0-30 minutes before attention and administration of care, that a significant proportion of the patients remarkably improved before allowed for trial leave, and that there is a high level of relatives’ satisfaction with nursing care services. Hypothetical finding shows that there is statistical significant difference in relatives’ satisfaction with nursing services based on the Wards/Units (p<0.05). It was recommended among other things that nurses should avoid beating patients when they are wrong and should upgrade from manual to online payment transaction with use of Point of Sale (POS).